Refractive outcomes of cataract surgery in patients with intrastromal femtosecond laser treatment of Presbyopia (INTRACOR) - Naujokaitis, Tadas; Hallak, Mustafa; Blöck, Louise; Khoramnia, Ramin; Auffarth, Gerd U. (Journal of refractive surgery, 2023)
PURPOSE: - - To evaluate the outcomes of cataract surgery with intraocular lens (IOL) implantation in patients who underwent intrastromal femtosecond laser treatment of presbyopia (INTRACOR). - - METHODS: - - This was an interventional case series of 8 patients (10 eyes) who presented for cataract surgery 6.1 ± 3.2 years (mean ± standard deviation [SD]) after INTRACOR (Technolas Perfect Vision GmbH) treatment. A monofocal IOL was implanted in 9 eyes (7 patients) and a small-aperture IOL was implanted in 1 eye. The IOL power was calculated without adjustments using biometry obtained after the INTRACOR treatment. For additional calculations, keratometry obtained before the INTRACOR treatment was used. Postoperative examinations included visual acuity testing, manifest refraction, defocus curve, ocular biometry, corneal tomography, aberrometry, anterior segment optical coherence tomography, and slit-lamp examination. - - RESULTS: - - After the cataract surgery, the mean ± SD uncorrected distance visual acuity was 0.37 ± 0.17 logMAR, the corrected distance visual acuity was 0.10 ± 0.10 logMAR, and the manifest refraction spherical equivalent, adjusted to infinity, was +0.39 ± 0.63 diopters (D). Intermediate and near visual acuity, both uncorrected and distance-corrected, and distance-corrected defocus curves varied considerably among patients. Using biometry performed after INTRACOR, the traditional IOL power calculation formulas produced hyperopic outcomes, with the mean ± SD prediction error ranging from +0.72 ± 0.34 to +0.96 ± 0.41 D. Although the mean ± SD prediction error decreased (range: −0.34 ± 0.56 to −0.15 ± 0.53 D) when using keratometry obtained before INTRACOR, the accuracy remained low due to high variability. - - CONCLUSIONS: - - In patients with cataract who had previous INTRACOR treatment, IOL power calculation could be inaccurate, with a tendency toward hyperopic outcomes. These results require confirmation in more extensive studies. - - [J Refract Surg. 2023;39(10):676-682.]